Ultrasound method in the diagnosis of ovarian neoplasms in patients with endometrial cancer - M. A. Chekalova; M. A. Shabanov; I. V. Torosyan; V. S. Kryazheva (ABV-press, 2017)
We analyzed the results of ultrasonic and postoperative histological examination of 300 patients with a primary diagnosis of uterine cancer who were treated at the cancer research center during the period from January to December 2014. After comprehensive examination all patients were performed surgical treatment in the various volumes. Histological examination of postoperative material of the uterus abnormal formation in the ovaries were detected in 42 (14 %). The most characteristic ultrasound signs of ovarian tumors both malignant and benign.